The Holocaust : a reader - Gigliotti, Simone, 1973- 1973- (Blackwell, 2005)
This book is divided into six chronological sections and thematic subsections that deal with current debates about the origins, implementation, and postwar interpretation of the Holocaust. Included throughout are oral histories and testimonies of both victims and perpetrators, from Jewish council leaders, to ghetto and concentration camp victims, to SS officials and German soldiers, which bring to light how underlying historical attitudes and policies evolved.